A Context-based Recommendation Model for Design Thinking Techniques Selection in Software Development - Parizi, Rafael; Marczak, Sabrina (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14617, 2020)
Design Thinking (DT) has been chosen as an approach to support problem-solving by many software development companies. However, there are divergences between the professionals of these companies concerning which techniques are performed, which steps are followed, and the way to implement this approach, as it proposes itself, to be divergent to generate numerous alternatives and, also, convergent, to find a solution. As a practical way to apply DT in software development, a collection of techniques are implemented during different working spaces provided by the DT models. Therefore, selecting the appropriate techniques within the set of the available ones is challenging. Aiming to present a solution for helping software development professionals in how to select the appropriate techniques for DT activities, we propose the development of a theoretical context-based recommendation model for selecting DT techniques for software development. Thus, we aim to develop a recommender and collaborative system of DT techniques and to validate it through industry-based empirical studies. We have already characterized the DT techniques that professionals are using and how they select them, and the benefits and challenges of using DT. These results were used to inform the proposal and the validation of a first version of the DT techniques recommendation tool, which presents the tool first round of core features.